The Impact of the COVID-19 Pandemic on Software Business Enterprises in Pakistan: Analysis and Implications - Haroon, Sundus; Zeeshan, Qasim (Acadlore Publishing Services Limited, 2023)
The COVID-19 pandemic emerged over three years ago as a public health crisis, swiftly evolving into a worldwide economic crisis with far-reaching implications for global business enterprises and industries. The unprecedented disruption has varied across sectors, with some experiencing severe consequences while others have thrived. As governments and economies continue to recover from the pandemic’s effects, it is crucial to analyze and comprehend these impacts to foster sustainable growth and prepare for future disruptions. This study aims to examine the COVID-19 pandemic’s ramifications on Pakistan’s software business enterprises by addressing three exploratory research questions: a) the pandemic’s influence on Pakistan’s software business enterprises, b) actions and initiatives undertaken by these enterprises during the pandemic, and c) the contributions made by these enterprises in combating the pandemic. Employing a mixed-methods approach, a survey research design was developed, incorporating both quantitative and qualitative methods to create a questionnaire grounded in a literature review. The findings of the survey are presented and discussed in-depth. This research contributes to the expanding body of knowledge on the COVID-19 pandemic’s effects on business enterprises and industries. © 2023 by the author(s).
Keywords: COVID-19; Disruption; Global industries; Pandemic; Software enterprises